SKRINING FITOKIMIA DAN BIOAKTIVITAS EKSTRAK AKAR Uncaria nervosa Elmer (BAJAKAH) - Maulina, Sheli; Pratiwi, Djihan Ryn; Erwin, Erwin (JURNAL ATOMIK, 2019)
One type of Bajakah that is believed by local people especially in the area of Muara Badak, KutaiKertanegara Regency, has the efficacy of anticancer drugs, is Uncaria nervosa Elmer. The purposes of this studywere to determine the content of secondary metabolites and the toxicity of the extracts of the bark and root of thewood of Bajakah (U. nervosa). From the results of phytochemical tests showed that both bark and root woodcontain secondary metabolites of alkaloids, flavonoids, terpenoids, and phenolics. Moreover, based on the result ofthe mortality test for Artemia salina shrimp larvae, it showed that both the bark and wood of the roots are verytoxic with LC50 values of 1.76 and 2.66 ppm, respectively. Both of these extracts are potentially cytotoxic to cancercells.